ANALISIS KINERJA BIDAN DALAM MELAKSANAKAN PENCEGAHAN INFEKSI PADA PERTOLONGAN PERSALINAN DI BIDAN PRAKTEK SWASTA (BPS) KOTA PADANG TAHUN 2005 - Mohanis Mohanis; Ulvi Mariati; Fatmi Arma; Henri Budi (Jurnal Kesehatan Masyarakat Andalas, 2008)
In Padang 2004, there were 10 maternal death from 13.923 life birth, and 30% were attended by midwife. Infection was 10% as a cause of all maternal death. It can be concluded that infection was one of the maternal death causes due to inadequate on doing infection prevention on delivery. Infection prevention is one of the "Five red yarn" that has be taken in giving safe and clean delivery services. Present of puerperal infection was an indicator on quality obstetric services that given by midwife on delivery process and also an indicator on midwifes quality services. It is a descriptive analytic research with cross sectional design. Population included all private practice midwife in Padang (n 300). Sample was taken by proportional random sampling (81 sample). Data were collected from November 1" till December 31s' using questionnaire and observation. There were no significant relationship on ages and period of practice with midwife quality services, but there were significant relationship on educational grade and training with midwife quality services.